BASIC PREVENTION: PENINGKATAN PENGETAHUAN IBU HAMIL DAN BALITA DESA SUMBERPINANG DALAM PENCEGAHAN STUNTING - Lailatul Karomah; Annisa Permatasari; Karina Aulia Nabila; Wahyu Zakariya; Dyah Ayu Kusuma Wardhani; Radika Audina Putri; Tegar Yuda Pratama; Denok Risky Ayu Paramita (Jurnal SADEWA, 2024)
Stunting is a disturbance of growth and development in toddlers due to malnutrition. Stunting is a serious problem in several cities in Indonesia, in the East Java region, specifically the Jember Regency, 19,870 in 2019. The most common stunting problem occurs in the northern part of the Jember health center, one of which is the Pakusari health center, so it must be addressed immediately. The purpose is to find out mother's knowledge about stunting before and after socialization related to stunting in toddlers in the Sumberpinang Pakusari area. This study used the pre-test and posttest methods. The sample used was 20 respondents. The results of this counseling showed that the knowledge of pregnant women and mothers of toddlers before and after being given education about stunting increased, this is evidenced by an average pretest score of 79.5 and a posttest score of 96 so that participants experience an increase of 16.5%.